(untitled) (Al-Academy, 2023)
The purpose of the research is to describe and analyse the content of visual declarations directed at Saudi society in the light of the sociology of culture, to determine their subjects and to identify the main objectives of visual declarations and their cultural components, the study population consists of fixed visual advertisements, directed at Saudi society, the study sample was selected in an intentional way, numbering 50 ads, fixed during the 2016-2022 period, the research was based on the analytical descriptive approach, and the study sample content analysis card was designed, the study concluded that the promotion of commercial products and services is the most common subject, the contents of the most widely used visual advertising elements are (Arabic language, avoiding deception and misinformation, observing the political values of the Saudi society - advertisements free of phrases, and the indecent images - their compatibility with religious teachings), ratios decreased in terms of (taking into account the family values of the Saudi society - the ads fit with the customs, traditions and customs of the Saudi society - staying away from the transfer and translation of ads of other societies - not exaggerating and aimless costing - meeting the cultural desires and needs of the community - enhancing the ads for the cultural identity of the community), the most important recommendations preparing studies on the design of visual advertisements using the survey tool and knowing the opinions of society in terms of sociocultural, preparing studies on the methods of visual advertisements in the Kingdom in terms of aesthetic and design, developing advertising methods using contemporary tools that enable the user to interact with advertisement.